Riset Akuntansi Managemen: Telaah Tiga Perspektif - Nahartyo, Ertambang; Utami, Intiyas (JURNAL RISET MANAJEMEN SEKOLAH TINGGI ILMU EKONOMI WIDYA WIWAHA PROGRAM MAGISTER MANAJEMEN, 2015)
The purpose of this paper is to discuss the development of management accounting research from three perspectives: reserach topics, theoretical foundations, and research methods. We base our discussion on previous literature reviews in the US, Australia, China, Finland, and other countries. We propose research opportunities in the field of management accounting in Indonesia. We argue that certain topics such as budgeting, performance evaluation, and management accounting techniques implementation are still interesting topics to study further in Indonesia context. As many studies have supported theoretical and practical development, we conjecture that management accounting research in Indonesia should be conducted to answer the question of ?what does happen? instead of ?what should happen?. In line with the conjecture, we contend that research is to focus on practicality aspects and the endeavor to find new frontiers in management accounting practice.Keywords: management accounting research, management accounting theory